Survey Keterampilan Teknik Dasar Tenis Lapangan Pada Atlet Tenis Kota Medan - Nurkhadri Nurkhadri; Gres Nina Natalia Br Sembiring; Apul Danikesuma Ginting; Chrismanto Panjaitan; Martinus Vincent Debataraja; Everanza Perdana Ginting (CV. Ulil Albab Corp, 2023)
This study aims to determine the extent basic tennis technic skill. The method in this study uses a survey method with data collection technique using tests and measurements. The instrument used in this study was the Service, Forehand and backhand test. The subjects in this study were 10 athletes in the Tennis club Medan. The results of this study indicate that the basic technic skills are categorized as